Nutritional and Pharmacological Properties of Agro-Industrial By-Products from Commonly Consumed Fruits - Wan Ishak, Wan Rosli (Universiti Sains Malaysia, 2018)
Presently, there is growing interest to use agricultural wastes as by-products for further exploitation as food additives or supplements. The waste product which is typically thrown into the environment has been re-vealed to exhibit certain nutritional and pharmacolog-ical properties. Some functional compounds have been reported to exert significant nutritional and pharmacological properties such as antioxidant, anti-cancer, antidiabetic, antimicrobial, etc. Based on re-cent literature, many reports or studies focused on the utilization and pharmacological effects of some se-lected agro-industrial by-products. This trend could provide the theoretical basis for further rational de-velopment and utilization of the waste for the thera-peutic and health purposes. Keywords: fruits by-products, fruits waste, nutrition-al value, pharmacological properties